2014
DOI: 10.1007/s40095-014-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Management and exploitation of direct normal irradiance resources for concentrating solar collectors: Algeria as a case study

Abstract: The use of concentrating solar collectors which are used in solar thermal power plant and concentrated photovoltaic systems implies that these systems only work with the direct normal irradiance (DNI). Unfortunately, DNI ground-based measurements are rarely available at the location of interest, this lack of DNI data contrasts with the availability of global and diffuse horizontal irradiance data (GHI, DHI). Nowadays, several spatial databases that estimate DNI have been developed; however, these databases pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Contrary to the flat plate solar collectors that benefit from global solar radiation, the main input variable of any CSP (concentrated solar power) system is the DNI [10]. By satellite measurements, the atlas data PVGIS (photovoltaic geographical information system) allowed us to estimate the site's energy potential [11].…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the flat plate solar collectors that benefit from global solar radiation, the main input variable of any CSP (concentrated solar power) system is the DNI [10]. By satellite measurements, the atlas data PVGIS (photovoltaic geographical information system) allowed us to estimate the site's energy potential [11].…”
Section: Resultsmentioning
confidence: 99%
“…monthly and annual direct solar radiation, regardless the availability or not of diffuse and GSR measurements. Then, they have found that compared to measurements in Algiers, Ghardaïa and Tamanrasset, the estimated data gave better results than those provided by five spatial databases, especially for the monthly averages values where an RMSE of 0.491 was obtained for the site of Ghardaïa [33]. In [34], 11 empirical models have been studied, correlating the monthly mean daily HGSR with air temperature and monthly mean sunshine duration, at 6 Algerian sites that are Algiers, Oran, Batna, Ghardaïa, Bechar and Tamanrasset (Figure 12).…”
Section: Semi-empirical and Parametric Modelsmentioning
confidence: 99%
“…Por ejemplo, Meteonorm [109], NASA SSE [131], SOLEMI [116] y SoDa [52]. En las referencias [90] y [134] se pueden encontrar comparativas entre distintas bases de datos de radiación solar directa.…”
Section: Datosunclassified